2007
DOI: 10.1186/1750-1326-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of α-synuclein increases amyloid plaque accumulation in a transgenic mouse model of Alzheimer's disease

Abstract: Abstractα-synuclein is a small soluble, cytosolic protein which associates with vesicular membranes. It is a component of intracellular Lewy bodies present in Parkinson's disease and a subset of Alzheimer's disease (AD). In addition, early studies identified a fragment of α-synuclein in the amyloid plaques of AD patients. Hypothesizing that α-synuclein might modify the AD pathogenic process, we crossed the Tg2576 strain of APP transgenic mice onto an α-synuclein knockout background to determine the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…They concluded that synucleins played important role during development and the aging process. Others have implicated synucleins in Alzheimer's disease (Kallhoff, Peethumnongsin, & Zheng, (2007). In our own work, we have reported significant decreases in neurodegeneration-related proteins (viz., amyloid precursor protein; APP) that may be related to the hippocampus gene expression levels we have observed, as well (Gatewood et al, 2005).…”
Section: Hippocampal Neuronal Gene Expressionmentioning
confidence: 48%
“…They concluded that synucleins played important role during development and the aging process. Others have implicated synucleins in Alzheimer's disease (Kallhoff, Peethumnongsin, & Zheng, (2007). In our own work, we have reported significant decreases in neurodegeneration-related proteins (viz., amyloid precursor protein; APP) that may be related to the hippocampus gene expression levels we have observed, as well (Gatewood et al, 2005).…”
Section: Hippocampal Neuronal Gene Expressionmentioning
confidence: 48%
“…[17] Formation of amyloid fibrils occurs neither from the folded conformation nor from a completely unstructured state but from some partially structured state capable of aggregating. [15,[31][32][33] We therefore conclude that the degree of residual structure and restriction of dynamics in hLys relative to those of the homologous hewl correlate with the increased tendency of hLys to form amyloid fibrils. This conclusion is further supported by data of hLys recorded at different concentrations ( Figure 2 top and Figure S2-S5 in the Supporting Information): increased R 2 relaxation rates and in particular scatter in the regions of clusters 1, 2, 4, 5, and 6 are observed at higher protein concentration, while the R 1 , hetNOE, and R 1rho values remain qualitatively the same regardless of concentration.…”
mentioning
confidence: 68%
“…In our previous study, APP transgenic mice also showed an increased expression of α-synuclein , which is the precursor of the non-amyloid-beta component of plaques (Kallhoff et al 2007). We discovered that icariin reduced the Aβ content and amyloid plaque deposition in the hippocampus of APPV717I transgenic mice (Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 91%